Ownership and governance, scope, and empowerment: how does context affect enterprise systems implementation in organisations in the Arab World?. Issue 4 (4th July 2021) - Bala, Hillol; Hossain, Mohammad Mobashar; Bhagwatwar, Akshay; Feng, Xuan
ABSTRACT: Research on enterprise systems (ES) implementation has focused on different aspects of implementation challenges, employee reactions, and system success. Much of this research has been conducted in developed countries and a few developing countries. This raises an obvious question about the applicability of findings to other contexts with different social and organisational cultures. We examine ES implementations in 12 organisations in Saudi Arabia, an important economic and political frontier and a unique sociocultural context in the Arab World. Using sociotechnical systems theory and institutional theory and the literature on contextualisation, we studied contextual aspects of three important factors related to ES implementations – i.e., ownership and governance, scope management, and employee empowerment. We found that the nature of ownership and governance plays a significant hindering role during implementation. Further, Saudi organisations implementing ES faced major challenges in managing the scope of implementation due to interferences from the top management and/or owners, and lack of justification by the consultants. Finally, we found that owners and top management were deeply concerned about losing their control over employees following ES implementations. We extend prior research and theories by offering contextual explanations unearthed from a context that is different from developed and many developing countries.